Assessment of Sleep Quality in Adolescents with Overweight and Obesity Using the Adolescent Sleep Hygiene Scale (ASHS) - Eleftheria Kampani; Eleni P. Kotanidou; Vasiliki Rengina Tsinopoulou; Evdoxia Sapountzi; Stergianna Ntouma; Evangelos Pavlou; Assimina Galli-Tsinopoulou (MDPI AG, 2024)
Background: Adolescent overweight and obesity are a public health problem with an epidemic trend. There is growing evidence that sleep quality correlates to body weight. The aim of this study was to investigate, sleep quality in adolescents with obesity/overweight. Methods: A total of 100 adolescents with overweight/obesity aged 12-18 years were enrolled. Anthropometric parameters were recorded and a laboratory investigation in the fasting state [glucose, insulin, cholesterol (TC), high-density lipoprotein cholesterol (HDL), low-density lipoprotein cholesterol (LDL), triglycerides, uric acid and glycated hemoglobin (HbA1c)] was performed. Insulin resistance was calculated by the Homeostasis Model Assessment of Insulin Resistance index (HOMA-IR). Sleep quality was assessed with the Adolescent Sleep Hygiene Scale (ASHS) questionnaire. Results: According to ASHS, 93% of the participants were classified as "Good Sleepers" (GSs) (score > 3.8) and 7% as "Poor Sleepers" (PSs) (score < 3.8). PSs had a statistically higher body mass index (BMI) compared to GSs (p = 0.026). Increased body mass index (BMI) (r = −0.306, p = 0.002), fast insulin (r = −0.224, p = 0.027), and HOMA-IR (r = −0.260, p = 0.010) exerted a negative effect on sleep quality. Controlling for lipids and uric acid, only TC levels appeared to have a statistically significant and specifically positive correlation with the ASHS score (r = 0.202, p = 0.045). HbA1c values and waist circumference tended to be negatively correlated, but not significant to adolescent sleep quality [(r = −0.101, p = 0.330), (r = −0.095, p = 0.359), respectively]. The influence of central obesity on the ASHS score was also explored, but no correlation was found (p = 0.566). Conclusions: Sleep quality, as reflected by the ASHS score, was associated negatively with BMI, fasting insulin levels, and insulin resistance. Furthermore, a gender difference was observed, as adolescent males were found to achieve a higher overall ASHS score compared to females.